Coagulation and thrombomodulin in response to exercise of different type and duration - Weiss, Claus; Welsch, Bärbel; Albert, Michael; Friedmann-Bette, Birgit; Strobel, Günther; Jost, Joachim; Nawroth, Peter Paul; Bärtsch, Peter (Medicine and science in sports and exercise, 1998)
Coagulation and thrombomodulin in response to exercise of different type and duration. Med. Sci. Sports Exerc., Vol. 30, No. 8, pp. 1205-1210, 1998. - Purpose: - The present study was conducted to evaluate the role of the duration of exercise and the impact of the exercise type for exercise-induced activation of coagulation. - Methods: - Eleven male triathletes were subjected to stepwise maximal (17 min) and 1-h maximal exercise in swimming, cycling, and running. Changes of hemostatic variables and of plasma thrombomodulin, a marker of endothelial cell activation, were monitored. - Results: - Irrespective of the type of exercise, alterations in markers of thrombin (prothrombin fragment 1 + 2, thrombin-antithrombin III complexes) and fibrin formation (fibrinopeptide A) were more pronounced after 1-h exercise than after stepwise maximal exercise. Hemostatic parameters rose to the highest levels after running resulting in substantial fibrin formation as indicated by fibrinopeptide A increasing from 1.33 ng·mL−1 to 2.25 ng·mL−1 (P < 0.05) after 1-h exercise testing. Significant changes of plasma thrombomodulin were detected exclusively after running with increases from 38.2 ng·mL−1 to 44.2 ng·mL−1(1 h, P < 0.01). - Conclusions: - The data demonstrated that prolonged exercise is necessary for exercise-induced activation of coagulation resulting in thrombin and fibrin formation and suggested that endothelial cell activation possibly due to mechanical factors associated with running might play a role.